A simple inverse analysis method for eddy current-based measurement of through-thickness conductivity of carbon fiber composites. (August 2018) - Mizukami, Koichi; Watanabe, Yudai
Abstract: A simple inverse analysis method is proposed to measure the through-thickness conductivity of carbon fiber reinforced plastic (CFRP) laminates using eddy current testing. Finite element analyses were performed to investigate the relationship between the eddy current sensor signal and the anisotropic conductivity of a cross-ply CFRP. It was found that the resistive component of the impedance of the eddy current sensor changed with the through-thickness conductivity of CFRP, while the conductivity in the transverse direction had almost no influence on the sensor impedance. Using this characteristic and the conductivity in the fiber direction determined by fiber volume fraction, the through-thickness conductivity of a CFRP laminate was estimated from the resistive component of the impedance of the eddy current sensor. Experimental studies showed that the through-thickness conductivity estimated by the proposed eddy current testing method was in good agreement with that measured by the four-probe method. The proposed eddy current method enables fast and non-contact measurement of the through-thickness conductivity of CFRP laminates. Highlights: Measurement of through-thickness conductivity of carbon fiber composites is required for assurance of lightning protection property. An eddy current testing method is developed to measure the through-thickness conductivity of multidirectional carbon fiber composite laminates. Finite element analyses show that the resistive component of the eddy current sensor is affected only by the through-thickness conductivity if the conductivity in the fiber direction is given. Experiments of the eddy current testing are performed for a cross-ply laminate and the through-thickness conductivity is estimated from the numerical analysis results. The through-thickness conductivity estimated from the eddy current testing is in good agreement with that measured by the four-probe method.